TYPES AND FUNCTIONS OF POLITENESS VIOLATION IN THE COURT SESSION “KOPI SIANIDA” - Inestie Printa Elisya (Salingka, 2018)
The court session is a formal legal meeting in which evidence about crimes. In session process, all of need is cooperation from all participants in order to make clear the case. This writing is aimed at identifying the types of politeness violated by the participant in the court session “KOPI SIANIDA”. The data are all the linguistic aspects involved in these sessions. In collecting the data, observational method with note-taking, recording and taking picture. The analysis is done by referential method related to the concept proposed by Oktavianus and Revita (2013). Having analyzed the data, it is found that there are four types and four functions indicated as politeness violation. The types are (1) politeness in expressing; (2) politeness in being emotional; (3) politeness in asking; and (4) politeness in refusal. The functions are (1)expressive; (2)informative; (3) descriptive; and (4) argumentative.